GENERAL IN AIR AND SPACE LAW - Z. Z. Khalilov (Научный вестник МГТУ ГА, 2016)
The article deals with the study of link between air and space law, the problem of determining the boundaries of the airspace is investigated. The international practices of various institutions of air and space law, in particular, in Europe, Argentina, Turkey, and the practice of studying these issues in joint form within the research Institute of the Republic of Azerbaijan are analyzed.